Comparison of Outsourced Workers' Protection Under the Manpower Law and the Job Creation Law - Suyatno Suyatno (Faculty of Law, Universitas Pekalongan, 2022)
Employment is regulated by Law Number 13 of 2003 concerning Manpower (Manpower Law). The relationship between workers and employers is formalized through agreements, which are then divided into fixed-term employment agreements (PKWT) and indefinite-term employment agreements (PKWTT). Additionally, there is outsourcing, which involves the recruitment of employees through manpower supply companies. The approach used in this research method is normative juridical research, where the analysis is based on an approach to legal regulations as the main elements of the study. The reduction of business risks often leads to the practice of outsourcing, which frequently involves the transfer of tasks to outsourcing companies. However, in reality, outsourcing workers often suffer more disadvantages compared to the benefits received by the companies. Hence, the Job Creation Law was enacted as a form of legal protection for the increasingly prevalent outsourcing workers. However, one of the policies in the Job Creation Law includes the removal of provisions from the Manpower Law that previously allowed outsourcing workers to become permanent employees or to establish more stable employment relationships with the employing companies.